A poética de Paulo Hecker Filho - Klumb, Mateus (2021)
In this work, a first study on Paulo Hecker Filho’s published poetic literature has been developed. Having worked as a poet, critic, short-story, novel and drama writer, translator and Brazilian editor, the author is an important, even though he is not much studied, exponent of Rio Grande do Sul literature. His work counts with dozens of books published, as well as a collection, currently available at DELFOS – Espaço de Documentação e Mémoria Cultural, a cultural space located at PUCRS, which supplies researchers with an extense list of materials for studying. In the following study, panoramically, a profile of this multi-facet author has been built, so that it is possible to identify his space and connections with the inner Gaucho literary system and with the national literary system as well. Futhermore, having use of literature theories, it has been elaborated an approach which aims to present the writer’s published poetic works, highlighting a list of characteristics of Heckerian’s poetry, which needs to be deeply and methodically analysed in studies which would have this purpose. By poiting the author’s profile, the importance and relevance of his engagement, the development of Gaucho literature is highlighted, so as the necessity of having developed studies which comprehend a vast research material, result of a life dedicated to the literary art. The aesthetic characteristics at Hecker Filhos’s work still await for studies interested in doing a formal analysis and they also provide, according to the results obtained from an early incursion, endless possibilities for the literary theory, literary history, critical genetics studies, among others.